SUSTAINABLE DEVELOPMENT OF ENTERPRISE: ESSENCEAND CALCULATION INTEGRAL INDEX OF SUSTAINABLEDEVELOPMENT OF AIRLINES - Tatjana S. Rotar; Vaspur G. Niazyan (Статистика и экономика)
The article is devoted to one of the essential tasks of the enterprise - sustainable development. The article discusses different views on the term sustainable development of the enterprise. Based on their analysis, the authors conclude that the sustainable development of enterprises should be considered as a single process, whose goal is the continuous improvement of the main economic indicators of the enterprise. The article proposes a system of partial indices, method of determining the composite index of sustainable development of the enterprise, which includes three pillars: sustainable technological development, sustainable human development and sustainable business development, as well as the calculation of indices for sustainable commercial development on the example of three Air Transport companies Russian Federation.